ANALISIS SEARCH ENGINE OPTIMIZATION (SEO) PADA UMKM DOA IBU KOSMETIK DI TOKOPEDIA - Sarah Fahdah Afifah; Irfan Ardiansah (Politeknik Ubaya, 2023)
The existence of social restrictions during the COVID-19 pandemic has had many impacts, one of which is limiting direct sales of SMEs. One of them is Doa Ibu Kosmetik which sells various personal needs like cosmetics and body care. Doa Ibu Kosmetik opens a digital shop through Tokopedia to encourage sales. Search Engine Optimization (SEO) method was implemented in the Tokopedia account to compete with others. The method used to optimize the shop page is to upgrade the shop's status to Power Merchant and activate the features provided by Tokopedia. Product page optimization is carried out by adding titles, prices, descriptions, and product photos so that they comply with Tokopedia's recommendations and can compete with other sellers. The TopAds feature, which is Tokopedia's paid advertising feature, has also been implemented to help increase traffic on the Tokopedia Doa Ibu Kosmetik page. The research results show that optimization on Tokopedia can increase visits and sales.